Potentiality of raloxifene loaded melittin functionalized lipidic nanovesicles against pancreatic cancer cells - Usama A. Fahmy; Shaimaa M. Badr-Eldin; Hibah M. Aldawsari; Nabil A. Alhakamy; Osama A. A. Ahmed; Mohamed F. Radwan; Basma G. Eid; Shaban R. M. Sayed; Gamal A. El Sherbiny; Walaa Abualsunun (Taylor & Francis Group, 2022)
Pancreatic cancer (PC) frequency and incidence have grown rapidly in recent years. One of the most serious problems with PC is the existence of asymptotic manifestations, which frequently delays early detection, and until the diagnosis is established, tumor cells progress to the metastatic stage. Another significant concern with PC is the scarcity of well-defined pharmacotherapeutic drugs. The aim of this study was to develop an efficient nanocarrier system to augment the efficacy of raloxifene (RLX) against PC cells. As a result, the current investigation was carried out in order to give an effective treatment method, in which an optimum RLX loaded phospholipid-based vesicles with melittin (PL-MEL) was chosen using experimental design software, with particle size, zeta potential and entrapment efficiency % as dependent variables. Furthermore, anticancer activity against PANC1 cells was assessed. The optimized nanovesicle parameters were 172.5 nm for the measured size, zeta potential of -0.69 mV, and entrapment efficiency of 76.91% that were in good agreement with the expected ones. RLX-raw, plain formula, and optimized RLX-PL-MEL showed IC50 concentrations of 26.07 ± 0.98, 9.166 ± 0.34, and 1.24 ± 0.05 µg/mL, respectively. Furthermore, cell cycle analysis revealed that the nanovesicle was most effective in the G2-M phase, whereas Bax, and Bcl-2 estimates revealed that optimized RLX formula had the highest apoptotic activity among treatments investigated. However, as compared to RLX alone or plain formula alone, the optimized formula demonstrated higher expression of TNFα and Bax while a significant reduction of Bcl-2 and NF-κB expression was observed. mitochondrial membrane potential (MMP) analysis confirmed the apoptosis as well as the anticancer effect of the optimized formula. Thus, the present study results showed an improvement in the anti-PC effects of the RLX with phospholipid conjugated melittin, making it a novel treatment approach against PC.